2014
DOI: 10.1111/ane.12346
|View full text |Cite
|
Sign up to set email alerts
|

Attention and CERAD test performances in cognitively impaired elderly subjects

Abstract: Our data demonstrate the relative independency of the CERAD-Plus on the variability of attention and particularly alertness suggesting its robustness in psychiatric memory clinic settings. Moreover, CERAD-Plus subtests correlated considerably with failure rates in divided attention, suggesting that impairment in divided attention tasks may be early markers of cognitive impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The CERAD‐PLUS is an established cognitive test battery originally developed as a screening for Alzheimer´s disease and designed to test executive functions, visuospatial understanding, language, and memory function through 12 subtests 16,18,19 . Table 1 displays a short description of the applied subtests following our previously published methodology 20 …”
Section: Methodsmentioning
confidence: 99%
“…The CERAD‐PLUS is an established cognitive test battery originally developed as a screening for Alzheimer´s disease and designed to test executive functions, visuospatial understanding, language, and memory function through 12 subtests 16,18,19 . Table 1 displays a short description of the applied subtests following our previously published methodology 20 …”
Section: Methodsmentioning
confidence: 99%
“…Lastly, sporadic AD involves the progressive age-related mis-regulation of numerous neurobiological pathways at multiple molecular, genetic, epigenetic, behavioral, cognitive, mnemonic, neurochemical, and neurophysiological stages. If advanced next generation RNA-sequencing and/or high density microfluidic array-based profiles of AD tissues or biofluid samples are any indication of AD variability then there are real and significant differences in AD onset, incidence, epidemiology, disease course, severity, and progression amongst different human populations (Guerreiro et al, 2012 ; Lukiw, 2013b ; Qiu et al, 2014 ; Walhovd et al, 2014 ; Barnes et al, 2015 ; Blennow et al, 2015 ; Verhülsdonk et al, 2015 ; Wang et al, 2015 ; Zhao et al, 2015 ; Roth et al, 2016 ). It is therefore unlikely that any single miRNA in the CSF, blood serum or any other biofluid compartments from multiple human populations will represent an equal therapeutic target for every case of AD, and it would be equally unlikely that any single AM strategy would be applicable to the clinical management of every AD patient.…”
Section: The Heterogeneous Nature Of Mirna Expression In Ad Brainmentioning
confidence: 99%
“…What might be particularly advantageous, however, for significantly improved future sporadic AD therapeutics would be a highly interactive, “ personalized medicine” approach. This would involve a comprehensive evaluation of multiple AD deficiencies including, prominently, miRNA- and mRNA-based gene expression alterations, AD-relevant DNA mutations, pro-inflammatory biomarkers, and amyloid-peptide load in the CSF, blood serum and other biofluids, combined with data from MRI- and PET-based brain imaging, and familial and clinical history and lifestyle factors that together would be extremely useful in the improvement of directed therapeutic strategies (Lau et al, 2014 ; Walhovd et al, 2014 ; Baumgart et al, 2015 ; Blennow et al, 2015 ; Gui et al, 2015 ; Hill et al, 2015a , b ; Østergaard et al, 2015 ; van Harten et al, 2015 ; Verhülsdonk et al, 2015 ; Wang et al, 2015 ; Wu et al, 2015 ). Anti-miRNA (AM) therapeutic approaches seem particularly attractive since alteration in miRNA abundance appears to occur at relative early “ initiator” or “ propagatory” stages of the AD process while NF-kB inhibition may have too many unwanted off-target effects (Figure 1 ).…”
Section: The Heterogeneous Nature Of Mirna Expression In Ad Brainmentioning
confidence: 99%
“…Accordingly, this culminates in a remarkably heterogeneous neuropathological scaffold for AD, with significant variations in disease onset, progression, severity of neuropathology, extent of behavioral and cognitive deficits, and memory loss ( 4 12 ). To cite one very recent example, a relatively large epidemiological study of AD patient data ( N = 7815) ( 12 ) indicated significant heterogeneity in the first cognitive/behavioral symptomatic “indicator” experienced by AD patients ( 13 16 ). In other recent studies, two laboratories have independently reported significant variation in the miRNA-34a-mediated triggering receptor expressed in myeloid/microglial cells-2 (TREM2) down-regulation in an African-American population that further underscores (i) the importance of investigating different ethnic populations for AD epigenetic risk; (ii) intrinsic variance and human biochemical and genetic individuality ; and (iii) allelic heterogeneity and potentially diverse pathogenic contributory mechanisms to the AD process (sufficient TREM2 is important in the clearance of excessive Aβ peptides from the brain) ( 9 16 ).…”
mentioning
confidence: 99%
“…Related to these observations are studies that over the last 15 years have indicated that gene expression patterns at the messenger RNA (mRNA) level, Aβ peptide load, SP and NFT densities and localization, and familial and clinical histories further underscore AD heterogeneity ( 8 12 , 17 20 ). Indeed, there appears to be intrinsic limitations of useful AD biomarkers because just one biomarker cannot define the mechanism of AD, by nature are associative and/or correlative, and are unable to unequivocally prove disease causality ( 13 17 , 21 23 ). For example current genome-wide association studies (GWAS), whole-exome and whole-genome sequencing have revealed mutations in excess of 20 genetic loci associated with AD risk ( 11 , 19 , 20 , 24 ).…”
mentioning
confidence: 99%